Efektifitas Pemerintahan Desa Dalam Menggerakan Partisipasi Masyarakat di Desa Karangbaru Kecamatan Cikarang Utara - Bunga Yuma Putri; Evi Priyanti; Kariena Febriantin (Jurnal Ilmiah Wahana Pendidikan, 2023)
Researchers used qualitative research methods. Qualitative research is research about descriptive research and tends to use analysis. The type of research where the findings are not obtained through statistical observations or other forms. Trying to understand and interpret the meaning of an event of human behavior interaction in a particular situation according to the researcher's own perspective. Qualitative methods seek to understand and interpret the meaning of an event of human behavior interaction in a particular situation from the perspective of the researcher himself. Research using qualitative research aims to understand the object under study in depth. Aims to develop the concept of sensitivity to problems that rule, explain the reality related to exploring the theory from below and develop an understanding of one or more of the phenomena that are understood. Data analysis was performed by reducing data, displaying data or presenting data, and drawing conclusions. The research was conducted in Karangbaru Village, Cikarang Utara District, Bekasi Regency on March 30, 2021. In a research that aims to believe that what an organization achieves depends on its ability to mobilize the community to advance village welfare. In this village there are already many organizations that are running well, such as the youth organization, LPM, and others. All of the youth in Karangbaru village are members of the youth organization, although there are some members who are not active because of other activities, but the village and the head of the youth organization have coordinated so that the performance of the youth organization will continue to be improved, especially during the pandemic. The process of integrating accurate and accurate communication communications by other organizations because there must be questions so as to be able to build good communication.